Structure Elucidation, Total Synthesis, Antibacterial In Vivo Efficacy and Biosynthesis Proposal of Myxobacterial Corramycin. Issue 51 (21st November 2022) - Couturier, Cédric; Groß, Sebastian; von Tesmar, Alexander; Hoffmann, Judith; Deckarm, Selina; Fievet, Anouchka; Dubarry, Nelly; Taillier, Thomas; Pöverlein, Christoph; Stump, Heike; Kurz, Michael; Toti, Luigi; et al.
Abstract: Herein, we describe the myxobacterial natural product Corramycin isolated from Corallococcus coralloides . The linear peptide structure contains an unprecedented (2 R, 3 S )‐γ‐ N ‐methyl‐β‐hydroxy‐histidine moiety. Corramycin exhibits anti‐Gram‐negative activity against Escherichia coli ( E. coli ) and is taken up via two transporter systems, SbmA and YejABEF. Furthermore, the Corramycin biosynthetic gene cluster (BGC) was identified and a biosynthesis model was proposed involving a 12‐modular non‐ribosomal peptide synthetase/polyketide synthase. Bioinformatic analysis of the BGC combined with the development of a total synthesis route allowed for the elucidation of the molecule's absolute configuration. Importantly, intravenous administration of 20 mg kg −1 of Corramycin in an E. coli mouse infection model resulted in 100 % survival of animals without toxic side effects. Corramycin is thus a promising starting point to develop a potent antibacterial drug against hospital‐acquired infections. Abstract : Corramycin is a novel natural product produced by the myxobacterium Corallococcus coralloides . The structure, extraordinary total synthesis and biosynthesis of the antibiotic is described for the first time. Its promise as an in vivo septicemia model, the absence of cross‐resistance with commonly used antibiotic classes, and the lack of cytotoxicity make Corramycin a potential new drug in the fight against multidrug‐resistant pathogens.